Transnacionalização das políticas públicas: a atuação brasileira no Haiti como novo paradigma jurídico de intervenção humanitária - Alves, Geovane Machado (Universidade do Vale do Rio do Sinos, 2009)
In a brief look at the current socio-political international environment, it appears that the world has gone through an important period of its history, which, among other factors, the rapid growth in the number of armed conflicts. However, the traditional multilateral system of peaceful settlement of disputes has shown little effectiveness and legitimacy in the face of this serious problem. In this context, this dissertation has as main objective to verify the possibility of building a new legal paradigm of humanitarian intervention, based essentially on principles of solidarity and non-indifference, as well as the duty of care and affinity. In other words, this research attempts to legal analyze and philosophical translation that could be given to the idea of diplomacy solidarity. Thus, it is considered that, alongside the military intervention and diplomacy traditional and emerging role of a third matrix that is the evolution of international cooperation for the promotion of public policies. The structure
Keywords: cooperação Sul-Sul; diplomacia solidária; políticas públicas; solidariedade internacional; transnacionalização; intervenção humanitária; diplomacy solidarity; international solidarity; public policies; south-south cooperation; transnationalization; humanitarian intervention; Ciências Sociais Aplicadas